Understanding the Importance of Generation Z’s Eyewear Choices: The Role of Online and Offline Shopping Experiences in Fashion Products - Dewi, Wafiq Aulia Sukma; Dellyana, Dina (Eduvest - Journal of Universal Studies, 2024)
This study examines factors influencing Generation Z's purchase intentions in the eyewear market in South Tangerang, Indonesia, focusing on service quality, brand consciousness, social media influence, and online shopping. Using Structural Equation Modeling (SEM), the research identifies intermediate constructs such as perceived value, brand trust, and customer trust, which shape purchasing decisions. The findings show that service quality is the most significant factor in shaping perceived value, which in turn impacts purchase intention. Brand consciousness influences brand trust, while social media significantly affects brand trust and loyalty. The study also highlights that online shopping experiences have a stronger impact on trust than offline shopping, reflecting Gen Z's digital preferences.